2021
DOI: 10.1111/jgh.15399
|View full text |Cite
|
Sign up to set email alerts
|

Post‐marketing analysis for biosimilar CT‐P13 in inflammatory bowel disease compared with external data of originator infliximab in Japan

Abstract: Background and Aim: CT-P13, an infliximab (IFX) biosimilar, was approved for treatment of inflammatory bowel disease. However, no comparison with the originator IFX in this indication has been conducted in Japan where endemic levels of tuberculosis and hepatitis virus infection are not low. We evaluated the safety and efficacy in real-world data of CT-P13 and compared with originator IFX data in Japan. Methods: In a prospective post-marketing surveillance (PMS) study, patients who received CT-P13 in a 28-month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Infliximab biosimilars CT-P13 and SB2 were approved in 2016 and 2017, respectively, and both have similar therapeutic efficacy and safety profiles compared to infliximab and induced comparable liver injury compared to infliximab. 62 Other biologics such as levilimab (targeting interleukins or the receptors), satralizumab and cytokine or chemokine-targeted biologics such as mavrilimumab and otilimab are still used in clinical trials. Although different biosimilars have demonstrated efficacy and safety compared to the reference product, serious adverse reactions may not have been fully identified and confidence in their use is still lacking.…”
Section: Othersmentioning
confidence: 99%
“…Infliximab biosimilars CT-P13 and SB2 were approved in 2016 and 2017, respectively, and both have similar therapeutic efficacy and safety profiles compared to infliximab and induced comparable liver injury compared to infliximab. 62 Other biologics such as levilimab (targeting interleukins or the receptors), satralizumab and cytokine or chemokine-targeted biologics such as mavrilimumab and otilimab are still used in clinical trials. Although different biosimilars have demonstrated efficacy and safety compared to the reference product, serious adverse reactions may not have been fully identified and confidence in their use is still lacking.…”
Section: Othersmentioning
confidence: 99%
“…En otro estudio japonés sobre la vigilancia poscomercialización, los pacientes que recibieron infliximab CT-P13 en un periodo de 28 meses a partir de enero de 2015 fueron seguidos durante 2 años. No hubo diferencias en la incidencia de tuberculosis y de lesión hepática al comparar con el biológico original (tuberculosis: 2 pacientes [0.31%] con CT-P13 y 10 pacientes [0.24%] con el biológico original, p = 0.75; lesión hepática: 18.5% con CT-P13 y 15.4% con el biológico original, p = 0.22) 22 .…”
Section: Experiencia En El Uso De Biocomparables En La Eii En Asiaunclassified
“…Recently, a few studies outside North America have compared safety outcomes, such as hepatitis and tuberculosis infections, and the pharmacokinetic profile of infliximab biosimilar and the originator in the real-world IBD population. These studies found that infliximab biosimilar had similar safety and pharmacokinetic profile in real-world settings [9,10]. Additional real-world studies from outside North America, where approval for infliximabdyyb for IBD occurred before 2016, suggest no clinically meaningful differences in safety and effectiveness when patients either remain on RP infliximab or switch to an infliximab biosimilar [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 97%